Actual issues of the pathogenesis of COVID-19 and possible measures for the prevention of severe forms of the disease - Kh. G. Omarova; V. V. Makashova; Zh. B. Ponezheva; D. V. Usenko; A. V. Gorelov; V. I. Pokrovsky (Лечащий Врач, 2021)
The enormous impact of SARS-CoV-2 infection and the insufficiency or lack of established and evidence-based therapeutic measures give rise to fundamental and clinical studies to examine the mechanisms of penetration of the virus into the human body and its subsequent effects on the body. The uniqueness of the pathogenesis of the infection caused by SARS-CoV-2 is primarily due the virus tropism to the receptors angiotensin-converting enzyme type 2 (ACE2), which are on the surface of various cells: pneumocytes, epithelials of the esophagus and intestines, cardiomyocytes, endotheal capillaries, urinary and nervous system, as well as in other organs. It is assumed that the suppression of ACE2, induced by penetration of SARS-CoV-2 into cells, may be particularly harmful for subjects with pre-existing ACE2 deficiency. These considerations provide justification for the study of the role of therapeutic approaches conceptually associated with the activity of the ACE2 receptor.